Syakhshiyah Visa in the Implementation of Independent Hajj: A Perspective from Sadd al-Dzarī‘ah - Zulfendri Syarqawi; Ansari Ansari; Nurasiah Nurasiah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to explain and analyze the implementation of the independent Hajj using the Syakhshiyah visa from a sadd al-dzarῑ‘ah perspective. This research is qualitative legal research, using an empirical juridical approach. Data sources in this research are divided into two, namely primary and secondary. Primary data was obtained from field research through observation. Meanwhile, secondary data includes all statutory documents, government regulations, as well as all bibliographic references related to research. Data from field and library research were analyzed qualitatively using descriptive analytical techniques. This research proves that carrying out the Hajj independently using a shakhshiyah visa from a sadd al-dzarῑ‘ah perspective is Haram. This is proven by: first, the pilgrims' lack of understanding of the Hajj regulations. Second, some congregations still do not comply with the statutory regulations. Third, there is no security guarantee for pilgrims. Fourth, it can cause damage to pilgrims using official visas. The findings in this research indicate that carrying out the independent Hajj using a Syakhshiyah visa is not in line with Maqāshid Al- Syarῑ‘ah in Islam.